EGCG inhibits the oxidative damage induced by TiO2-NPs in human colon cell lines: EGCG inhibits the oxidative damage of TiO2-NPs - Wang, Han; Li, Xiang; Xu, Yundong; Tian, Yaping; Li, Qidan; Zhang, Yongzhen; Wang, Xu; Ni, Juan (Cellular and Molecular Biology, 2024)
To assess the protective effects of (-)-Epigallocatechin-3-gallate (EGCG), a natural antioxidant, against cellular oxidative damage induced by titanium dioxide nanoparticles (TiO2-NPs), Human Colon cells NCM460 and Colon Cancer cells SW620 were selected for this study. The cells were divided into three groups: control group, TiO2-NPs (80 μg/mL) exposure group, and EGCG (20 μmol/L)+TiO2-NPs (80 μg/mL) co-exposure group. The study evaluated the precipitation rate of TiO2-NPs influenced by EGCG in a cell-free system. It also measured the levels of ROS, MDA, and total antioxidant capacity in the cells of each group. The uptake of TiO2-NPs by the cells was assessed using the SSCe/SSC0 ratio, and genome instability was evaluated. The results demonstrated that the addition of 20 μmol/L EGCG to the system resulted in greater sedimentation of TiO2-NPs compared to TiO2-NPs alone (P<0.05). The SSCe/SSC0 values in the co-exposure group were significantly lower than those in the TiO2-NPs alone group (P<0.001). TiO2-NPs induced a higher oxidative stress index in the cells (P<0.001), while the co-exposure group exhibited a lower REDOX index (P<0.001). The combination of EGCG and TiO2-NPs did not significantly affect genome instability in either cell line. Importantly, EGCG showed a certain inhibitory effect on oxidative damage to colon cells induced by TiO2-NPs, with no significant difference observed between normal and cancer cells in terms of this protective effect. Conducting a comprehensive investigation into the interaction mechanism between EGCG and TiO2-NPs is crucial for establishing a scientific foundation that can guide the optimal utilization of the antioxidant properties of EGCG to mitigate the toxicity associated with TiO2-NPs.